2006
DOI: 10.1017/s0376892906003432
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive value of participatory biodiversity monitoring in community forestry

Abstract: In the context of action research in community forests, stakeholders' values for biodiversity can be elicited, communicated and understood with the help of a multidimensional conceptual framework. This incorporates levels of diversity (genes, species, habitats and processes), types of values (direct use, indirect use, option and existence) and stakeholders. This paper explores the effect of using this framework on forest monitoring, learning and communication, and wider implications for conservation, in Baglun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 53 publications
2
30
0
2
Order By: Relevance
“…Despite the threats and challenges, this CBM network has empowered people to take ownership of problems, consistent with findings elsewhere (Lawrence et al 2006), and has proved to be a successful way to manage and mitigate a hazard, as has been shown elsewhere, e.g. Anderson et al (2010).…”
Section: Threats To Network Stability and Effectivenesssupporting
confidence: 75%
See 1 more Smart Citation
“…Despite the threats and challenges, this CBM network has empowered people to take ownership of problems, consistent with findings elsewhere (Lawrence et al 2006), and has proved to be a successful way to manage and mitigate a hazard, as has been shown elsewhere, e.g. Anderson et al (2010).…”
Section: Threats To Network Stability and Effectivenesssupporting
confidence: 75%
“…Concurrently the practice of enlisting the help of lay volunteers to monitor and record a natural process has become widespread over the last decade, particularly in the fields of ecology and natural resource management; this practice is often referred to as 'citizen science' and has given rise to a burgeoning research literature (Conrad & Hilchey 2010;Gura 2013). Studies in those fields have demonstrated that 'citizen scientists' can both provide good quality data (Tulloch et al 2013;Parsons et al 2011) and prompt community management of important biodiversity issues (Lawrence et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Thinking together with the community about the variables likely to lead to sustainable management almost always entails a preliminary discussion on the ways to connect their daily use and understanding of natural resources and processes to formal concepts like ''management,'' ''sustainability,'' and ''biodiversity'' (Lawrence et al 2006;Purnomo et al 2005). These discussions give rise to opportunities to take stock of the different threats to the environment and propose coping strategies and possible solutions, reinforcing environmental awareness in the community (Andrianandrasana et al 2005;Poulsen and Luanglath 2005;Tiani and Bonis-Charancle 2007).…”
Section: Environmental Awarenessmentioning
confidence: 99%
“…The implementation of a local monitoring system should reinforce the role of local communities as managers or co-managers of natural resources by giving due importance to their TEK and at the same time involving them formally in sustainable resource management Fraser et al 2006;Lawrence et al 2006). This empowerment of local institutions happens in two phases, at the time the monitoring system is created and then when it is implemented.…”
Section: Reinforcement Of Local Institutionsmentioning
confidence: 99%
“…As noted by Cantarello et al (2014) and , this could potentially be achieved by adopting a participatory forest management approach, where local people are actively involved in forestry activities. In recent years, there has been increasing interest in such participatory approaches in many countries, illustrated by the CAMPFIRE project in Zimbabwe (Taylor 2009) and the development of Community Forest User Groups in Nepal (Lawrence et al 2006). In order to introduce such approaches to Kyrgyzstan, such approaches will need to be adapted to the prevailing pattern of land ownership.…”
mentioning
confidence: 99%